Maternal anxiety levels with the success of exclusive breastfeeding: A correlation study - Margaretha Lisa Purwaningsih; Heru Subaris Kasjono; Nanik Setiyawati (Jurnal Kesehatan Ibu dan Anak, 2022)
UNICEF and WHO is calling on the government and all stakeholders to maintain and promote access to services that allow the mother to continue breastfeeding during the pandemic COVID-19. As a result, the access of an essential service such as counseling, nursing in hospitals, health clinics, and through a visit to the house interrupted. The information is not right that circulating about the safety of breastfeeding has lowered the number of nursing mothers because of the fear of transmitting the disease to her child.The aim of this study was to determine the relationship of maternal anxiety levels with the success of exclusive breastfeeding on the pandemic COVID-19. The Study used the observational analytic design with Cross Sectional Study. Sampling with Accidental Sampling technique. Retrieval of data using a questionnaire Google Form. Analysis used Chi-Square test. The result state that there is no relationship between the level of anxiety with the success of exclusive breastfeeding with p value 0.064 (>0.05). The majority of respondents was not at risk, higher education, family income in the top categories, and have the experience. There is no relationship with the level of anxiety of the mother with the success of exclusive breastfeeding.